1976
DOI: 10.1128/jvi.18.1.365-369.1976
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptase activity and genome composition of defective influenza virus

Abstract: Eight genome RNA segments are present in both normal and von Magnustype influenza virus preparations and all species are transcribed by the virionassociated polymerase. Although both the RNA polymerase activity and the amount of the three largest RNA segments are reduced in defective influenza virus preparations, these reductions do not appear to be great enough to account for the much greater loss of infectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Experiments are now in progress to define more specifically the role of the M protein in influenza virus replication and to examine the question of whether the RIFMLF tsb3 FMI on August 17, 2020 by guest http://jvi.asm.org/ Downloaded from synthesis of M protein is indeed a rate-limiting step in virus production (6,9). It should be noted that there are eight influenza virus genes (1,12,17,20,22) and that ts mutants have been identified for all of the influenza A virus genes except gene 8, which codes for the nonstructural protein. We are presently attempting to identify mutants with defects in this protein.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments are now in progress to define more specifically the role of the M protein in influenza virus replication and to examine the question of whether the RIFMLF tsb3 FMI on August 17, 2020 by guest http://jvi.asm.org/ Downloaded from synthesis of M protein is indeed a rate-limiting step in virus production (6,9). It should be noted that there are eight influenza virus genes (1,12,17,20,22) and that ts mutants have been identified for all of the influenza A virus genes except gene 8, which codes for the nonstructural protein. We are presently attempting to identify mutants with defects in this protein.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of large RNA species from von Magnus particles has been observed consistently (1,3,7,18,22), but exactly what gene segment(s) was lost has not been determined unambiguously. The finding in our previous study (17) and this study and the study made by Janda et al (10) showed that the loss of polymerase genes varied from one von Magnus preparation to another, just as the species of extra RNAs contained in them were variable.…”
Section: Discussionmentioning
confidence: 99%
“…NAYAK ET AL. reports indicated that DI viruses lack entirely or contain only reduced amounts of the largest segment of viral RNA (4, 6, 23). However, this view that DI influenza viruses lack a specific RNA segment has been disputed by a recent observation which suggests that influenza DI viruses do not selectively lose a specific RNA segment (2). There are a number of major difficulties in studying DI influenza viruses.…”
mentioning
confidence: 99%